2019
DOI: 10.1002/chem.201901758
|View full text |Cite
|
Sign up to set email alerts
|

Redox‐Induced Oxidative C−C Bond Cleavage of 2,2′‐Pyridil in Diruthenium Complexes

Abstract: In the recent years, there has been an emerging research interest in the domain of C−C bond‐cleavage reactions. The present contribution deals with the redox‐mediated dioxygen activation and C−C bond cleavage in a diruthenium complex [(acac)2RuII(μ‐L1)RuII(acac)2], 1 (acac=acetylacetonate) incorporating 2,2′‐pyridil (L1) as the bridging ligand. The above process leads to a C−C‐cleaved monomeric product [(acac)2RuIII(pic−)], 2 (pic−=piconilate). Intriguingly, similar diastereomeric complexes [(acac)2RuII(μ‐L2)R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 68 publications
1
15
0
Order By: Relevance
“…Interestingly, the structure of 1 also showed that β‐ketoiminate moiety allied to the picolinoyl fragment of coordinated L1′ dangling outward from the chelate ring formed by L1′, which might have extended the preferred orientation for the facile oxygenation at its C α instead of its cyclization as reported earlier (Scheme 1). [4a] Structural parameters involving {Ru(acac) 2 } fragment in both 1 and 3 are in agreement with the reported analogous systems [4a,5] …”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Interestingly, the structure of 1 also showed that β‐ketoiminate moiety allied to the picolinoyl fragment of coordinated L1′ dangling outward from the chelate ring formed by L1′, which might have extended the preferred orientation for the facile oxygenation at its C α instead of its cyclization as reported earlier (Scheme 1). [4a] Structural parameters involving {Ru(acac) 2 } fragment in both 1 and 3 are in agreement with the reported analogous systems [4a,5] …”
Section: Resultssupporting
confidence: 85%
“…Metal based anisotropic EPR (Δ g =0.38–0.57, Figure 2 and Table 2) along with metal dominated calculated Mulliken spin density (Ru>0.75, Figure 3 and Table 3) implied {Ru III −L′ − } and {Ru III −L′} electronic form for 1 , 3 and 2 + , respectively [5,8,9] . Moreover, the higher g anisotropy along with greater extent of spin localization onto the metal center in complex 3 supported the decreasing covalency with respect to 1 and 2 + which in effect disfavored the delocalization of spin into the ligand backbone.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…In the following year, Lahiri and co‐workers reported dioxygen activaton by a 2,2'‐pyridyl bridged diruthenium framework (13) (Figure c) . The redox accessibility at both the metal and the ligand centers allows for the formulation of the redox tautomeric form 14 which in turn activates the dioxygen leading to the formation of a mononuclear ruthenium picolinate complex by an oxidative cleavage of C–C bond.…”
Section: Ligand Assisted Bond Activationmentioning
confidence: 99%